Introspection of Indian Agriculture with Respect to Food Security and Agricultural Sustainability - Singh, M.B.; Kumar, Santosh (National Geographical Journal of India, 2022)
Alarmingly high population pressure in the country has led to fast decline in availability of arable land from 0.69 ha in 1991 to merely 0.15 ha in 2011. In order to feed huge population of 1211 million (2011) of the country, food demand would need to be increased to 345 million tons by 2030. However, net cultivated area is stagnating since last 30 years. Besides, response to fertilizer application in food grain production is declining steadily. Per capita calorie intake is decreasing in both rural and urban areas. Thus time has come to introspect agricultural scenario of the country for achieving food and nutritional security and agricultural sustainability